PENDAMPINGAN KADER POSYANDU MELALUI PENINGKATAN KAPASITAS KOMUNIKASI DALAM MENYAMPAIKAN INFORMASI KESEHATAN MELALUI MEDIA DIGITAL - Khiyaroh, Intihaul; Elviana, Shofia (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2025)
This study aims to improve the communication capacity of Posyandu cadres in deliveringhealth information through digital media, especially using smartphones. Posyandu cadreshave a strategic role as a source of health information in the community, but so far thedissemination of information still relies on conventional media such as pamphlets andguidebooks which tend to be monotonous and ineffective. Through training to improve digitalbased communication skills, Posyandu cadres are taught to process and disseminate healthservice materials more creatively and practically using smartphones. The results of the studyshowed that this training succeeded in improving the ability of cadres to manage communityservice data and deliver health information more easily, quickly, and effectively. Thus, the useof digital media can strengthen the role of Posyandu cadres in public health education andsupport the improvement of the quality of Posyandu services as a whole.